1994
DOI: 10.1159/000098632
|View full text |Cite
|
Sign up to set email alerts
|

Italian Multicentric Study on Pain Treatment with Epidural Spinal Cord Stimulation

Abstract: A multicentric study on the treatment of nonmalignant chronic pain with epidural spinal cord stimulation (SCS) has been carried out in 32 Italian centers devoted to pain therapy. Neurosurgical and anesthesiology units participated in this retrospective study. 410 of the eligible patients were enrolled in the protocol: 48% were male, 52% female. All patients underwent a screening test period (average 21 days) and 74% underwent the definitive implant. The diagnosis was failed back surgery syndrome in 45%, reflex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
1
2

Year Published

1998
1998
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(45 citation statements)
references
References 0 publications
2
40
1
2
Order By: Relevance
“…In our study, the initial response rate of 87% dropped to 79% at 6 months but improved to 84% at 2 years due to a committed follow-up and maintenance program. Our complication and explantation rates were similar to previously published data [2,3]. If an SCS therapy program does not yield an initial response rate after implantation of at least 80% and a long-term effectiveness of 80% of the responders at 2-3 years, the tangible benefits of SCS could be lost and this therapy may become difficult to justify.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…In our study, the initial response rate of 87% dropped to 79% at 6 months but improved to 84% at 2 years due to a committed follow-up and maintenance program. Our complication and explantation rates were similar to previously published data [2,3]. If an SCS therapy program does not yield an initial response rate after implantation of at least 80% and a long-term effectiveness of 80% of the responders at 2-3 years, the tangible benefits of SCS could be lost and this therapy may become difficult to justify.…”
Section: Discussionsupporting
confidence: 84%
“…However, at 14-48 months, only 80% continued to have pain relief [1]. Another study demonstrated that the initial 87% success rate at 3 months dropped to 75% at 6 months, down to 69% at 12 months and to 58% at 24 months [3]. In our study, the initial response rate of 87% dropped to 79% at 6 months but improved to 84% at 2 years due to a committed follow-up and maintenance program.…”
Section: Discussioncontrasting
confidence: 43%
“…This method makes it difficult to determine how effective the stimulator was in treating the painful conditions. Some of these shortcomings were avoided by a large, multicenter Italian study published by Broggi et al [6]. They retrospectively report on the experience of 32 centers treating 410 patients with chronic pain.…”
Section: Recent Studiesmentioning
confidence: 99%
“…[6][7][8][9][10] Yapılan çalışmalar, kronik ağrı tedavisinde spinal kord stimülasyonu uygulamasının güvenli ve efektif olduğunu göstermiştir. [11,12] Bu yazıda lumbar disk hernisi nedeniyle operasyon geçiren ve sonrasında postlaminektomi sendromu gelişen ve SKS uygulanmasına rağmen sağ kalça ve bel bölgesinde ağrı şi-kayeti devam eden hastaya sağ kluneal sinir dağılım bölgesine oktad elektrod'un subkutan (SUBQ) olarak yerleştirildiği hastadan bahsedilmektedir. Kliniğimiz-de ilk defa uyguladığımız SKS ve SUBQ kombinasyonu ile elde ettiğimiz başarılı sonuçtan sözedeceğiz.…”
Section: Introductionunclassified